Epidemiology of leprosy in Italy (1920 – 2019): a comprehensive review on existing data - Riccò, Matteo; Vezzosi, Luigi; Balzarini, Federica; Mezzoiuso, Angelo Giosuè; Ranzieri, Silvia; Vaccaro, Fabrizio Giovanni; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Background and aims: Incidence of leprosy in Italy has declined steadily over the last century, but available evidence remains fragmentary. Our review aims to summarize available data on the epidemiology of leprosy cases in Italy. Methods: The following keywords were used to explore PubMed and Embase: leprosy, Hansen’s disease, (Mycobacterium) leprae, Italy, without any chronological restriction. Results: We identified a total of 39 reports, including 7 national reports, 11 international reports, 20 case reports. Notified leprosy cases were: 839 between 1925 and 1948; 434 between 1955 and 1979; 76 cases for the decade 1980-1989; 112 between 1990 and 1999; 62 between 2000 and 2009, and a total of 25 cases since 2009. Since 2003, 53% of all cases occurred in illegal residents. Focusing on individual cases, latency between early signs/symptoms and a proper diagnosis ranged between 2 and 20 years in 52.1% of individual cases. Conclusion: Imported cases of leprosy are responsible for most leprosy incidence in Italy, and social stigma, the unfamiliarity of healthcare professionals with such disorders, and difficulties of some high-risk groups to be appropriately assessed hint to a possible under-diagnosis. Professionals should be made more aware of the potential for leprosy incidence among patients from countries where the disease is endemic.